Study on strength characteristics of soft and hard rock masses based on thermal-mechanical coupling - Qiu, Liewang; Xie, Liangfu; Qin, Yongjun; Liu, Xuejun; Yu, Guangming (Frontiers in Physics, 2022)
For deep resource exploitation and engineering construction, the mechanical properties of soft and hard interbedded rock mass are important factors impacting engineering stability. Simultaneously, the influence of temperature on the strength of deep rock mass poses a significant obstacle to the exploitation of deep resources and the utilization of underground space. In this paper, the particle flow code (PFC2D) is utilized to establish the thermal-mechanical coupling numerical model of soft and hard interbedded rock mass, and then the uniaxial compression response of soft and hard interbedded rock mass following thermal damage is studied. The displacement and contact force produced by applying temperature, as well as the failure strength, strain, and crack development of the specimen after uniaxial compression is analyzed. The findings reveal that: (i) The peak displacement caused by applied temperature increases first and subsequently decreases with the increase of soft rock thickness ratio (Hs/H), whereas the peak displacement increases linearly with increasing temperature. The peak contact force varies in two stages with the increase of the soft rock thickness ratio (Hs/H), and with the same trends. (ii) As the soft rock thickness ratio increases (Hs/H), the number of cracks decreases steadily. When the soft rock thickness ratio Hs/H< 0.5, the relationship curve between vertical strain and crack changes in two stages: the stage of crack development along with the stage of vertical strain gradually increases with crack development. When the thickness ratio of soft rock Hs/H > 0.5, the relationship curve changes in three stages: crack development stage, vertical strain increase stage, and vertical strain increase stage with crack development. (iii) When the soft rock thickness ratio Hs/H< 0.5, the failure strength gradually decreases as soft rock thickness increases at the temperature T=100℃, 200℃. The failure strength gradually increases as the soft rock thickness increases in general at T=400℃. Soft rock thickness ratio Hs/H> 0.5, the failure strength increases with the increase of soft rock thickness at T=300℃, 400℃. At T=100℃, 200℃, the tendency of the failure strength changes less.